45Improving the optimization of cardiac resynchronization therapy: Does multipoint left ventricular pacing shorten the paced-QRS duration compared to the fusion-optimized intervals method?. (18th June 2020) - San Antonio, R; Pujol-Lopez, M; Jimenez-Arjona, R; Doltra, A; Alarcon, F; Trotta, O; Quinto, L; Garre, P; Sanchez, M; Arbelo, E; Roca-Luque, I; Guasch, E; et al.
Abstract: Funding Acknowledgements: Cardiac Pacing Scholarship from the Spanish Society of Cardiology (SEC) Background: Electrocardiogram-based optimization of cardiac resynchronization therapy (CRT) using the fusion-optimized intervals (FOI) method has demonstrated to improve both acute hemodynamic response and left ventricle (LV) reverse remodeling compared to nominal programming of CRT. FOI optimizes the atrioventricular (AV) and ventriculo-ventricular (VV) intervals to achieve the shortest paced-QRS duration. The recent development of multipoint pacing (MPP) enables the activation of the LV from 2 locations, also shortening the QRS duration compared to conventional biventricular pacing. Purpose: To determine if MPP reduces the paced-QRS duration compared to FOI optimization. Methods: This prospective clinical study included 25 consecutive patients who successfully received a CRT with MPP pacing capability. All patients were in sinus rhythm and had an PR interval below 250 ms. The QRS duration was measured with a 12-lead digital electrocardiography (screen speed of 200 mm/s) at baseline and using 3 different configurations: MPP, FOI and a combined FOI-MPP strategy. In MPP, the intervals were (based on previous studies): 1) AV 130 ms, 2) Right ventricular (RV)-LV2 (Δ1) 5 ms, and 3) LV1-LV2 (Δ2) 5 ms. In FOI, AV and VV intervals were optimized to achieve fusion between intrinsic conduction and biventricular pacing. In FOI-MPP, the Δ2 was set at 5 ms, while AV and Δ1 intervals were optimized using the FOI method. The CRT device was programmed with the configuration that achieved a greater paced-QRS shortening. After 45 days, battery life was estimated. Results: Mean age was 65 ± 10 years, 20 were men (80%) and baseline QRS duration was 177 ± 17 ms. The FOI method bested nominal MPP (QRS shortened by 58 ± 16 ms vs 43 ± 16 ms, respectively, p = 0.002). Adding MPP to the narrowest QRS by FOI did not result in further shortening (FOI: 58 ± 16 ms vs FOI-MPP: 59 ± 13 ms, p = 0.81). The final configuration was FOI method alone in most cases (n = 16, 64%) and FOI-MPP in all others (n = 9, 36%; figure). In total, 10 out of 25 patients (40%) were not candidates to MPP due to: 1) pacing thresholds exceeding 3.5 V/0.4 ms at the distal or proximal electrode (8, 32%), and 2) phrenic stimulation (2, 8%). Estimated battery longevity was longer in patients receiving FOI as compared to MPP (8.3 ± 2.1 years vs. 6.2 ± 2.2 years, p = 0.04). Conclusion: In CRT, the FOI method is not improved by coupling with MPP. Up to 40% of patients are not candidates for MPP due to high thresholds or phrenic stimulation. The use of MPP in unselected patients would result in a decrease of battery longevity, without any additional benefit over FOI.